Analisis Pola Nafkah Rumah Tangga Petani Kelapa Sawit Pada Masa Peremajaan Di Kecamatan Sungai Bahar Kabupaten Muara Jambi - Primadiptha Gevinanda, Ayu; Alamsyah, Zulkifli; Yanita, Mirawati (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
Sungai Bahar district is one of the districts inMuaro Jambi regency that relies on the plantation sector to increase the income. Rejuvenation is one of the efforts to increase the productivity of oil palm. Loss of farmers income in Sungai Bahar district occurs as long as the plants have not produced yet, so farmers must devote their family’s labor to sources of income based on livelihood patterns from the on farm, off farm and non farm agricultural sector. This study aimed to determine the allocation of household labor in meeting family needs, to determine the livelihood patterns of oil palm farmers in Sungai Bahar district and to analyse the income of oil palm farmers based on their income patterns. The coverage area of this studywere Mekar Sari Makmur Village, Panca Mulya Village, and Berkah Village. This studywere conducted using descriptive and quantitative methods through income analysis. The results of this study indicated that in Sungai Bahar District Muaro Jambi Regency allocated labor for on farm livelihoods (3.815 HOK/year (BPDPKS) and 2.194 HOK/year (independent)), off farm (3.209 HOK/year (BPDPKS) and 302 HOK/year (independent)), and non farm (8.448 HOK/year (BPDPKS) and 6.288 HOK/year (Independent)). The pattern of livelihood in thisstudy area during the oil palm rejuvenation period were the on farm’slivelihood sources: farming of shelled corn, peanuts and watermelon,the off farm’slivelihood source: oil palm farm labor, and the non farm’slivelihood source: workshops, traders, teachers, and private sector employees. The family income of oil palm farmers during the rejuvenation period of oil palm plants differed significantly based on the livelihood pattern.